CHARACTERIZATION OF Pr6O11 DOPED ZINC FLUOROBORATE GLASS - M PrajnaShree; Akshatha Wagh; Y Raviprakash; B. Sangeetha; Sudha D Kamath (European Scientific Journal, ESJ, 2013)
Pr3+ doped zinc fluoroborate glasses with the chemical composition [(mol %) 30ZnF2 – 20 TeO2 – (50-x) B2O3 – xPr6O11] (where x = 0.0, 0.1, 0.5, 1.0 and 1.5 mol %) of different concentration of rare earth element praseodymium (Pr3+) have been prepared by conventional melt quench technique. The physical parameters like density, refractive index, number density, molar refraction, molar electronic polarizability, electronic polarizability, dielectric constant, polaron radius, inter–ionic separation, molar volume and oscillator strength of these glasses were calculated as a function of dopant concentration. The densities and refractive indices of these glasses were found to be in the range 2.0 g/cm3 - 2.67 g/cm3 and 1.644 – 1.73 respectively. Stability of the glass doped with 1.0 mol % Pr3+ was found to be 120.